Pitfalls and Rewards for Implementing Ocular Motor Testing in Acute Vestibular Syndrome: A Pilot Project. Issue 2 (March 2017) - Dumitrascu, Oana M.; Torbati, Sam; Tighiouart, Mourad; Newman-Toker, David E.; Song, Shlee S.
Abstract : Objectives: Isolated acute vestibular syndrome (iAVS) presentations to the emergency department (ED) pose management challenges, given the concerns for posterior circulation strokes. False-negative brain imaging may erroneously reassure clinicians, whereas HINTS-plus examination outperforms imaging to screen for strokes in iAVS. We studied the feasibility of implementing HINTS-plus testing in the ED, aiming to reduce neuroimaging in patients with iAVS. Methods: We launched an institutional Quality Improvement initiative, using DMAIC methodology. The outcome measures [proportion of iAVS subjects who had HINTS-plus examinations and underwent neuroimaging by computed tomography/magnetic resonance imaging (CT/MRI)] were compared before and after the established intervention. The intervention consisted of formal training for neurologists and emergency physicians on how to perform, document, and interpret HINTS-plus and implementation of novel iAVS management algorithm. Neuroimaging was not recommended if HINTS-plus suggested peripheral vestibular etiology. If a central process was suspected, brain MRI/MR angiogram was performed. Head CT was reserved only for thrombolytic time-window cases. Results: In the first 2 months postimplementation, HINTS-plus testing performance by neurologists increased from 0% to 80% ( P =0.007), and by ED providers from 0% to 9.09% ( P =0.367). Head CT scans were reduced from 18.5% to 6.25%. Brain MRI use was reduced from 51.8% to 31.2%. About 60% of the iAVS subjects were discharged from the ED; none were readmitted or had another ED presentation in the ensuing 30 days. Conclusions: Implementation of HINTS-plus evaluation in the ED is valuable and feasible for neurologists, but challenging for emergency physicians. Future studies should determine the "dose-response" curve of educational interventions.